Effects of formulation on transport of pyrethroids in residential settings. (29th December 2015) - Jones, Russell L.; Trask, Jennifer R.; Hendley, Paul; Cox, Megan J.; Chepega, Joseph C.; Harbourt, Christopher M.; Davidson, Paul C.
Abstract: Washoff of 17 pyrethroid products resulting from a 1‐h, 25.4‐mm rainfall occurring 24 h after application was measured in indoor studies with concrete slabs. These products included different pyrethroid active ingredients and a range of formulation types. Based on this replicated study, 5 product pairs with contrasting washoff behaviors were chosen for an outdoor study using 6 full‐scale house fronts in central California. Products in 4 of these pairs were applied once to different rectangular areas on the driveway (1 product in each pair to 3 house lots and the other to the remaining 3 house lots). The products in the fifth pair were applied 3 times at 2‐mo intervals to vertical stucco walls above the driveway. All house lots received natural and simulated rainfall over 7 mo. Indoor studies showed differences up to 170‐fold between paired products, whereas the maximum difference between paired products in the field was only 5‐fold. In the pair applied to the wall, 1 product had 91 times the washoff of the other in the indoor study, whereas in the field the same product had 15% lower washoff. These results show that, although the formulation may influence washoff under actual use conditions, its influence is complex and not always as predicted by indoor experiments. Because the formulation also affects insect control, washoff research needs to be conducted together with efficacy testing. Environ Toxicol Chem 2016;35:340–347. © 2015 The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals, Inc. on behalf of SETAC.